2019
DOI: 10.1021/acs.bioconjchem.9b00217
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Conjugation to Phosphorothioate Oligonucleotides by Cu-Catalyzed Huisgen 1,3-Dipolar Cycloaddition

Abstract: Improving oligonucleotide delivery is critical for the further development of oligonucleotide-based therapeutics. Covalent attachment of reporter molecules is one of the most promising approaches toward efficient oligonucleotide-based therapies. An efficient methods for the attachment of a variety of reporter groups is Cu(I)-catalyzed Huisgen azide−alkyne 1,3dipolar cycloaddition. However, the majority of potential oligonucleotide (ON) therapeutics in clinical trials are carrying phosphorothioate (PS) linkages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
0
21
0
3
Order By: Relevance
“…However, until recently, there were almost no examples of conjugation reactions with phosphorothioates by the Cu(I)-catalyzed azide-alkyne cycloaddition, which was associated with the adverse influence of copper ions on the stability of the PS bond, giving rise to the impression that this type of click chemistry is incompatible with phosphorothioate oligonucleotides. The Strömberg group designed an optimized alkyne-azide cycloaddition protocol for the high-yielding synthesis of phosphorothioate conjugates [ 310 ]. The reaction was carried out by the fragment coupling method on the solid phase using either commercial or synthesized in-house PS oligonucleotides, easily obtainable linkers, and the copper (I) bromide-dimethyl sulfide complex as a catalyst.…”
Section: Post-synthetic Conjugation Approachesmentioning
confidence: 99%
“…However, until recently, there were almost no examples of conjugation reactions with phosphorothioates by the Cu(I)-catalyzed azide-alkyne cycloaddition, which was associated with the adverse influence of copper ions on the stability of the PS bond, giving rise to the impression that this type of click chemistry is incompatible with phosphorothioate oligonucleotides. The Strömberg group designed an optimized alkyne-azide cycloaddition protocol for the high-yielding synthesis of phosphorothioate conjugates [ 310 ]. The reaction was carried out by the fragment coupling method on the solid phase using either commercial or synthesized in-house PS oligonucleotides, easily obtainable linkers, and the copper (I) bromide-dimethyl sulfide complex as a catalyst.…”
Section: Post-synthetic Conjugation Approachesmentioning
confidence: 99%
“…Synthetic advantages of click chemistry were also exploited for the attachment of several entities to solid-supported oligonucleotides. In a recent work, Honcharenko et al [ 68 ] reported for the first time a method for the efficient conjugation of peptides to phosphorothioate oligonucleotides (PS-ON) ( Scheme 22 ). The use of phosphorothioate as a backbone is a widely employed strategy to enhance the pharmacokinetics and nuclease resistance of oligonucleotides [ 69 ], and to date, the majority of therapeutic ONs incorporate the PS backbone modification [ 43 ].…”
Section: Clicked Nucleic Acidsmentioning
confidence: 99%
“…Various methods have been developed for conjugation of specific ligands to ONs, either by in‐line conjugation (Zaramella, Yeheskiely, & Stromberg, ) or by post‐conjugation, either in solution (Juliano, Ming, & Nakagawa, ) or on solid phase (Jezowska, Honcharenko, Ghidini, Stromberg, & Honcharenko, ; Wenska et al., ). Use of Cu(I)‐catalyzed Huisgen azide‐alkyne 1,3‐dipolar cycloaddition (Honcharenko, Honcharenko, & Stromberg, ; Verma, ), known as “click reaction,” has been proven to be a highly efficient approach for conjugation of ONs to peptides, other ONs, the m 3 G‐CAP (Honcharenko et al., ; Honcharenko et al., ; Verma, ), small molecules like biotin (Jezowska, Romanowska, Bestas, Tedebark, & Honcharenko, ), or fluorophores and even for preparation of multiple conjugates (Jezowska et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…Taking this into consideration, we have developed a method employing the Cu(I) bromide dimethyl sulfide complex as a copper source for “click reaction” conjugations to PS‐ONs (Basic Protocol 1). The method allows for very efficient conjugation of reporter molecules to ONs and is fully compatible with a PS backbone (Honcharenko et al., ).…”
Section: Commentarymentioning
confidence: 99%